2018
DOI: 10.4103/aer.aer_145_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three different concentrations of levobupivacaine for epidural labor analgesia: Clinical effect and pharmacokinetic profile

Abstract: Background:The aim is to compare the clinical effect of three different concentrations of levobupivacaine (0.25%, 0.125%, and 0.0625%) on the sensory and motor block characteristics and mode of delivery during epidural labor analgesia. We also studied the pharmacokinetic profile of the three concentrations during labor.Materials and Methods:Sixty pregnant females undergoing normal vaginal delivery under epidural analgesia were divided into three groups according to the concentration of levobupivacaine used. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In our study, motor block was never observed in the top-up group and rare also in the PIEB group (1%), demonstrating that this automated administration device can preserve women ability of moving and assuming whatever position during labor and delivery. In literature, the incidence of motor blockade is usually significantly higher, ranging between 30 and 50% of labor epidural analgesia [13,[18][19][20][21][22]. Although Tixier and colleagues observed no differences in motor block by comparing levobupivacaine 0.0625% and 0.125% [23], there is a strong view that the risk of motor block increases with increasing concentration of local anesthetics and the use of continuous infusion [13].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, motor block was never observed in the top-up group and rare also in the PIEB group (1%), demonstrating that this automated administration device can preserve women ability of moving and assuming whatever position during labor and delivery. In literature, the incidence of motor blockade is usually significantly higher, ranging between 30 and 50% of labor epidural analgesia [13,[18][19][20][21][22]. Although Tixier and colleagues observed no differences in motor block by comparing levobupivacaine 0.0625% and 0.125% [23], there is a strong view that the risk of motor block increases with increasing concentration of local anesthetics and the use of continuous infusion [13].…”
Section: Discussionmentioning
confidence: 99%
“…Five studies were published between 2011 and 2021 (511 women) [9, 11–14]. A total of 147 women received high concentration, 194 received low concentration and 170 received ultra‐low concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were published between 2011 and 2021 (511 women) [9,[11][12][13][14]. A total of 147 women received high in the main analysis, but with wider credible intervals.…”
Section: Mode Of Delivery Limited To Papers Published In the Last 10 ...mentioning
confidence: 99%
“… 4 , 5 Motor blockade following epidural analgesia has been directly associated with the concentration of local anesthetic used; the higher the concentration of local anesthetic, the greater the motor blockade in the pelvic floor and lower limb muscles. 1 , 5 , 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…2,3 In addition, the strong motor blockade achieved following the administration of traditional epidural analgesia could be one of the factors prolonging the second stage of labor, increasing the risk of instrumental birth. 4,5 Motor blockade following epidural analgesia has been directly associated with the concentration of local anesthetic used; the higher the concentration of local anesthetic, the greater the motor blockade in the pelvic floor and lower limb muscles. 1,[5][6][7] In recent years, a new approach to epidural analgesia has emerged, known as low-dose epidural analgesia or walking epidural analgesia.…”
Section: Introductionmentioning
confidence: 99%